Is There any Government Debt Threshold in Four Selected Central European Countries? : Government Debt Threshold in Four Selected Central European Countries - Hsing, Yu (The European Journal of Applied Economics, 2021)
Based on an extended production function, this paper finds that there is no government debt threshold in Hungary and Slovakia and that the respective government debt thresholds in Czechia and Poland are estimated to be 27.51% and 46.86%, which are far less than the 90% threshold proposed by Reinhart and Rogoff. Therefore, the Reinhart-Rogoff hypothesis does not apply to Czechia, Hungary, Poland, and Slovakia.